Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How must $|z|=3|z-1|$ be factored so I end up with a circle, plugging in $z=x+iy$ seems to just up with square roots everywhere. Detailed steps is much appreciated, thanks!

share|cite|improve this question
Square it up!.. – Berci Feb 6 '13 at 22:37
Have u tried its a mess – DJ_ Feb 6 '13 at 22:38
And use that $|z|^2=z \bar{z}$. – coffeemath Feb 6 '13 at 22:39
Yes, we can also calculate with complex numbers, using $|z|^2=z\bar z$: $$z\bar z=9(z-1)\overline{(z-1)}$$ which you prefer. – Berci Feb 6 '13 at 22:41
up vote 2 down vote accepted

\begin{align*} z \overline{z} = 9 (z - 1)(\overline{z}-1) = 9 z \overline{z} - 9 z - 9 \overline{z} + 9 \\ 8 z \overline{z} - 9 z - 9 \overline{z} + 9 = 0 \end{align*} Now a circle is supposed to look like $$(z - a)(\overline{z} - \overline{a}) = r^2= z \overline{z} - a \overline{z} - \overline{a} z + |a|^2$$ So taking our old relation and diving by 8, we get \begin{align*} z \overline{z} - \frac{9}{8} z - \frac{9}{8} \overline{z} + \frac{9}{8} = 0 \\ z \overline{z} - \frac{9}{8} z - \frac{9}{8} \overline{z} + \frac{81}{64} = \frac{81}{64} - \frac{9}{8} = \frac{9}{64} \end{align*} So with some algebra we have a circle centered at $\frac{9}{8}$ with radius $\frac{3}{8}$.

For fun: you can view the locus of solutions $S$ as the inverse image of the unit circle of the fractional linear transformation $z \mapsto \frac{z}{3z-3}$. Conjugate points are sent to conjugate points and the center of $S$'s conjugate is $\infty$. Infinity maps to $1/3$ and the conjugate about the unit circle is $3$, so the inverse of that is $8/9$. Similarly I can find what is sent to 1 and that'll give me a radius.

share|cite|improve this answer
Thanks for showing all the steps much appreciated!!! – DJ_ Feb 6 '13 at 23:51

Using $z=x+iy$, we get $$x^2+y^2=|z|^2=9|z-1|^2=9((x-1)^2+y^2).$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.